CARBON EMISSIONS DISCLOSURE: A CONCEPTUAL STUDY - khoirul aswar (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
Long-term changes in local, regional, and global weather patterns brought on by human activity are referred to as climate change. Since the early 20th century, observations of climate change have been conducted, and the findings show that human activity—specifically, the combustion of fossil fuels—is the primary factor accelerating climate change. The purpose of this study is to demonstrate how gender diversity on the board of directors, firm size, and independent commissioners affects the disclosure of carbon emissions. Potential and existing investors can utilise the information from this study to help them make decisions about the disclosure of carbon emissions in light of environmental change.